PENGARUH DANA ALOKASI UMUM (DAU) DAN DANA ALOKASI KHUSUS (DAK) TERHADAP BELANJA MODAL (Survei pada Kabupaten/Kota di Provinsi Jawa Tengah Periode 2015-2018) - Kurnianingsih, Berty (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
This study aims to determine whether there is an effect of the General Allocation Fund (DAU) and the Special Allocation Fund (DAK) on Capital Expenditure. The population in this study were all Districts/Cities in Central Java, totaling 35 Districts/Cities in 2015-2018. Sampling in this study was carried out using purposive sampling method, the criteria in selecting the sample were met so that the total sample size was 35 Districts/Cities x 4 years, namely 140 data. The data analysis technique used is descriptive statistical analysis, panel data regression model selection, classic assumption test (normality, multicollinearity, autocorrelation, and heteroscedasticity), model accuracy test (F test), partial test (t test), determination coefficient test (R2) and using the eviews 11. The test results show that the DAU variable has a significant effect on Capital Expenditure, while the DAK variable has no significant effect on Capital Expenditure.